ADOPTION CHALLENGES OF INTEGRATED PEST MANAGEMENT (IPM) TECHNOLOGY AND COCOA PRODUCTION IN CROSS RIVER STATE, NIGERIA: THE ELUCIDATION AND WAY FORWARD - Eghosa Osas UWAGBOE; Anthony Eghe AGBONGIARHUOYI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Efforts to mitigate the effect of pest had been through the use of chemicals, which often leave residues in cocoa beans. The International Institute of Tropical Agriculture (IITA) in collaboration with Sustainable Tree Crop Programme (STCP) promoted Integrated Pest Management (IPM) in Nigeria. There is dearth of information on the challenges confronting cocoa farmers to use IPM hence a need for investigation. The study utilised a three-stage sampling procedure to select respondents from Cross River state. Trained farmers (10%) were selected using a systematic random sampling to obtain a total sample of 271. Field data were collected with Interview schedule on socio-economic, enterprise characteristics, and challenges faced by respondents in IPM adoption. Analysis was done with descriptive and inferential statistics. Pearson Product Moment Correlation (PPMC) was used to test hypothesis. The male respondents were 83.4% while the female were 16.6%. Very few (2.6%) of the respondents produced more than 4,000 kg of cocoa beans per annum. Age of farm with a weighed score of 244.5 was rated as the highest severe factor affecting IPM adoption. Negative relationship exists between challenges and adoption behaviour which was significant (r=-0.236, p=0.000). Challenges had high effect on adoption of IPM by cocoa farmers and yield was low. There is need for farm rehabilitation due to old age to boost yield and sustain cocoa production in the study area.